2020
DOI: 10.1007/s00535-020-01698-4
|View full text |Cite
|
Sign up to set email alerts
|

An expert review on the use of tenofovir alafenamide for the treatment of chronic hepatitis B virus infection in Asia

Abstract: Asia has intermediate-to-high prevalence and high morbidity of hepatitis B virus (HBV) infection. The use of guideline-recommended nucleos(t)ide analogs with high barrier to resistance, such as entecavir (ETV), tenofovir disoproxil fumarate (TDF), and tenofovir alafenamide (TAF), is one of the key interventions for curbing HBV infection and associated morbidity in Asia. However, there are some challenges to the use of ETV and TDF; while ETV is associated with high resistance in lamivudine (LAM)-exposed (especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 73 publications
(138 reference statements)
0
31
0
Order By: Relevance
“…In their study, Buti et al did not record the loss of HBsAg at all in patients treated with either tenofovir or entecavir for 48 weeks [28]. Charlton et al and Aziz et al have reported analogous outcomes [29,30]. It was very unlikely that we would see a case of phase-V chronic HBV in such a small sample size where all patients were treatment-naive.…”
Section: Methodsmentioning
confidence: 89%
“…In their study, Buti et al did not record the loss of HBsAg at all in patients treated with either tenofovir or entecavir for 48 weeks [28]. Charlton et al and Aziz et al have reported analogous outcomes [29,30]. It was very unlikely that we would see a case of phase-V chronic HBV in such a small sample size where all patients were treatment-naive.…”
Section: Methodsmentioning
confidence: 89%
“…ETV is associated with resistance in LAM-experienced (particularly LAM-refractory) patients, and bone and renal safety issues are a concern with TDF [ 18 , 19 ]. Therefore, it has been proposed that optimizing the use of TAF is suitable for NA therapy along with guidance on specific patient groups at risk of renal or bone disease LAM-experienced patients [ 20 , 21 ]. As for ETV, it has a large number of accumulating evidences, usage experiences, and cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In these regimens, TDF is often combined with either emtricitabine or lamivudine plus other compounds [36] , [37] . However, bone and renal safety is the main concern with TDF in clinical practice [40] .…”
Section: Clinical Significance Of 6 Approved Drugsmentioning
confidence: 99%